1996
DOI: 10.1007/s004240050198
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous presence of cAMP and cGMP exert a co-ordinated inhibitory effect on the agonist-evoked Ca2+ signal in pancreatic acinar cells

Abstract: The stimulation of the pancreatic acinar cells by physiological secretagogues, such as acetycholine (ACh), activates a well-established intracellular signalling pathway, which involves the generation of Inositol 1,4,5-trisphosphate (InsP3) and the release of Ca2+ from intracellular stores. Caffeine, which inhibits this agonist-evoked Ca2+ response reversibly and competitively also blocks the Ca2+ signal generated by the non-specific activation of the membrane guanine nucleotide-binding proteins (G-proteins). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Inhibition of PDE leads to accumulation of intracellular cyclic nucleotides. It has been shown that inhibition of PDE mimics the effect of caffeine on the agonist-evoked Ca 2ϩ response in pancreatic acinar cells (12) and on the contractility of gallbladder muscle (46). In the present study, we showed that several nonselective as well as cGMP-or cAMP-specific PDE inhibitors were capable of reproducing the caffeine-induced enhancement of Kir6.2/SUR1 single-channel currents in intact HEK293 cells (Fig.…”
Section: Caffeine-induced K Atp Channel Stimulation Involves Pde Inhisupporting
confidence: 59%
See 1 more Smart Citation
“…Inhibition of PDE leads to accumulation of intracellular cyclic nucleotides. It has been shown that inhibition of PDE mimics the effect of caffeine on the agonist-evoked Ca 2ϩ response in pancreatic acinar cells (12) and on the contractility of gallbladder muscle (46). In the present study, we showed that several nonselective as well as cGMP-or cAMP-specific PDE inhibitors were capable of reproducing the caffeine-induced enhancement of Kir6.2/SUR1 single-channel currents in intact HEK293 cells (Fig.…”
Section: Caffeine-induced K Atp Channel Stimulation Involves Pde Inhisupporting
confidence: 59%
“…It has been suggested that simultaneous increases of intracellular cAMP and cGMP by caffeine inhibit the agonist-evoked intracellular Ca 2ϩ response in pancreatic acinar cells (12). We thus performed the following experiments to determine whether accumulation of cAMP by inhibition of cAMP-hydrolyzing PDE affects the K ATP channel function.…”
Section: Inhibition Of Camp-specific Pde Effected Mild Enhancement Ofmentioning
confidence: 99%
“…Sensitization of IP 3 -mediated Ca 2ϩ release by increases in cAMP is not unique to brown fat and has been reported in other cell types, including hepatocytes (5,12,31,34), pancreatic ␤-cells (19), articular chondrocytes (9), and parotid acinar cells (30). The effect of cAMP increases in brown fat on IP 3 -mediated Ca 2ϩ release contrasts with other cell types, such as megakaryocytes, pancreatic acinar cells, and nonvascular smooth muscle, in which cAMP inhibits IP 3 -mediated Ca 2ϩ release (1,7,35). Not all cells responding to 10 M phenylephrine with Ca 2ϩ increases also responded to isoproterenol with Ca 2ϩ increases.…”
Section: Discussionmentioning
confidence: 92%
“…However, the concentration of secretin used in the AR4‐2J cell line (1 n m ) was much higher than the one used in our study (50 p m ). Moreover, another previous study indicates that the stimulation of the cAMP system partly suppress the ACh‐evoked [Ca 2+ ] i increase (Camello et al 1996). After excluding the above possibilities, it is supposed that the synergistic effect might occur at the channel protein level, and precise knowledge about the mechanism of I Ks modulation by Ca 2+ and by cAMP is necessary to understand the synergistic effect.…”
Section: Discussionmentioning
confidence: 96%